Contribution of Urease to Colonization by Shiga Toxin-Producing Escherichia coli - Steyert, Susan R. (American Society for Microbiology, 2012)
Shiga toxin-producing Escherichia coli (STEC) is a food-borne pathogen with a low infectious dose that colonizes the colon in humans and can cause severe clinical manifestations such as hemolytic-uremic syndrome. The urease enzyme, encoded in the STEC chromosome, has been demonstrated to act as a virulence factor in other bacterial pathogens. The NH(3) produced as urease hydrolyzes urea can aid in buffering bacteria in acidic environments as well as provide an easily assimilated source of nitrogen that bacteria can use to gain a metabolic advantage over intact microflora. Here, we explore the role of urease in STEC pathogenicity. The STEC urease enzyme exhibited maximum activity near neutral pH and during the stationary-growth phase. Experiments altering growth conditions performed with three phylogenetically distinct urease-positive strains demonstrated that the STEC ure gene cluster is inducible by neither urea nor pH but does respond to nitrogen availability. Quantitative reverse transcription-PCR (qRT-PCR) data indicate that nitrogen inhibits the transcriptional response. The deletion of the ure gene locus was constructed in STEC strain 88-0643, and the ure mutant was used with the wild-type strain in competition experiments in mouse models to examine the contribution of urease. The wild-type strain was twice as likely to survive passage through the acidic stomach and demonstrated an enhanced ability to colonize the intestinal tract compared to the ure mutant strain. These in vivo experiments reveal that, although the benefit STEC gains from urease expression is modest and not absolutely required for colonization, urease can contribute to the pathogenicity of STEC.